THE EFFECTS OF GRAMMAR MASTERY AND VOCABULARY MASTERY TOWARDS STUDENTS' READING COMPREHENSION IN EXPOSITORY TEXT - Etik Dwi Styaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2019)
The main aim of the research is to      find out whether  there is significant effects of    Grammar Mastery and Vocabulary    Mastery  towards Students’  Reading       Comprehension in        Expository Text.  The research was    conducted at    SMKN 1   Cikarang of tenth grade students with the total sample 40 students that randomly taken and at SMKN 2 Cikarang  of tenth grade students with the total samples 40 students that randomly taken.  The method used in the   research was a survey. Data   of grammar  mastery, vocabulary mastery  and reading comprehension were acquired    from the tests. The data was analysed using descriptive statistical method, multiple  correlation coefficient, determination  coefficient  and  regression analysis. To test     the statistics is used T test and F test .  The result of the research    concluded that  there are   significant  effect of    Grammar mastery and vocabulary mastery towards student’s reading comprehension in expository text.